Prevalence of impaired left ventricular systolic function and heart failure in a middle aged and elderly urban population segment of Copenhagen. Issue 12 (14th November 2003) - Raymond, I; Pedersen, F; Steensgaard-Hansen, F; Green, A; Busch-Sorensen, M; Tuxen, C; Appel, J; Jacobsen, J; Atar, D; Hildebrandt, P
Abstract : Objective: To assess the prevalence of impaired left ventricular systolic function and manifest heart failure in a general population aged 50–89 years. Design: In this cross sectional survey, participants filled in a heart failure questionnaire. ECG, blood tests, and echocardiography were performed. Setting: The study population was recruited from general practitioners situated in the same urban area and examined in a university hospital in Copenhagen, Denmark. Participants: 764 participants (432 women and 332 men, median (SD) age 66 (11) years) participated. The study population was stratified to include a minimum of 150 persons in each age decade. Main outcome measures: Prevalence of impaired systolic function and manifest heart failure. Results: The prevalence of systolic dysfunction (left ventricular ejection fraction ⩽ 40%) was more than twice as high among men (7.6%) as among women (2.6%). In the male population systolic heart failure (left ventricular ejection fraction ⩽ 40% and symptoms) was found in 1.8% of the 50–59 years age group and approximately doubled for each age decade to reach 13.9% in octogenarians. Among women systolic dysfunction increased from 0.8% to 4.3% in the same age groups. Asymptomatic cases accounted for 44.0% of all cases of systolic dysfunction in the male population and only 9.1% in the female population. Conclusions: In this age controlled population study impaired left ventricular systolic function and heart failure increased substantially with age and was more than twice as frequent among men as among women. Asymptomatic left ventricular dysfunction occurred more frequently in men than in women and was less prevalent with increasing age.